Optimization of photocrosslinkable resin components and 3D printing process parameters. (1st October 2019) - Guerra, Antonio J.; Lammel-Lindemann, Jan; Katko, Alex; Kleinfehn, Alex; Rodriguez, Ciro A.; Catalani, Luiz H.; Becker, Matthew L.; Ciurana, Joaquim; Dean, David
Graphical abstract: Abstract: The role of 3D printing in the biomedical field is growing. In this context, photocrosslink-based 3D printing procedures for resorbable polymers stand out. Despite much work, more studies are needed on photocuring stereochemistry, new resin additives, new polymers and resin components. As part of these studies it is vital to present the logic used to optimize the amount of each resin constituent and how that effects printing process parameters. The present manuscript aims to analyze the effects of poly(propylene fumarate) (PPF) resin components and their effect on 3D printing process parameters. Diethyl fumarate (DEF), bisacylphosphine oxide (BAPO), Irgacure 784, 2-hydroxy-4-methoxybenzophenone (HMB) and, for the first time, in biomedical 3D printing, ethyl acetate (EA), were the resin components under investigation in this study. Regarding printing process parameters, Exposure Time, Voxel Depth, and Overcuring Depth were the parameters studied. Taguchi Design of Experiments was used to search for the effect of varying these resin constituent concentrations and 3D printing parameters on the curing behavior of 3D printable PPF resins. Our results indicate that resins with higher polymer cross-link density, especially those with a higher content of PPF, are able to be printed at higher voxel depth and with greater success (i.e., high yield). High voxel depth, as long as it does not sacrifice required resolution, is desirable as it speeds printing. Nevertheless, the overall process is governed by the correct setup of the voxel depth in relation to overcuring depth. In regards to resin biocompatibility, it was observed that EA is more effective than DEF, the material we had previously relied on. Our preliminary in vitro cytotoxicity tests indicate that the use of EA does not reduce scaffold biocompatibility as measured by standard cytotoxicity testing (i.e., ISO 10993-5). We demonstrate a workpath for resin constituent concentration optimization through thin film tests and photocrosslinkable process optimization. Statement of Significance: We report here the results of a study of photo-crosslinkable polymer resin component optimization for the 3D printing of resorbable poly(propylene fumarate) (PPF) scaffolds. Resin additives are initially optimized for PPF thin film printing. Once those parameters have been optimized the 3D printing process parameters for PPF objects with complex, porous shapes can be optimized. The design of experiments to optimize both polymer thin films and complex porous resorbable polymer scaffolds is important as a guess and check, or in some cases a systematic method, are very likely to be too time consuming to accomplish. Previously unstudied resin components and process parameters are reported.